Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward and Peppard pada PT. XYZ - Imam Fathul Aziz; Dicky Pratama (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The rapid development of information technology in the digital era has transformed the way organizations conduct their business activities. Information systems are now viewed not merely as operational support tools but as strategic elements capable of providing added value, increasing efficiency, and strengthening a company's competitiveness. In the context of PT XYZ, a company engaged in inspection and certification services, the use of information technology has become a crucial part of daily work processes. However, the implementation of information systems at the branch level still faces several obstacles. Data and process integration is not yet fully optimized, while alignment between the systems used and business needs has also not been achieved. This condition has the potential to hinder the company from providing fast, accurate, and innovative services. Therefore, appropriate and sustainable strategic planning of information systems is necessary. This study uses the Ward and Peppard framework enriched with Value Chain analysis to identify value-added activities, SWOT to identify strengths, weaknesses, opportunities, and threats, and PEST to map external factors affecting the business. In addition, the McFarlan Strategic Grid is used to prioritize the application portfolio that aligns with the company's long-term goals. The results of this research are expected to be able to produce an information system strategy design that not only supports operational efficiency, but also encourages service innovation and increases the competitiveness of PT XYZ in the inspection and certification services industry.